Impact III. - Lepage, Jacques (Saint-Etienne : Musée d'Art et d'Industrie, 1978)
Audat, Jean-Baptiste ; Barès, Pierre ; Borsotto, Jean ; Broto, José Manuel ; Caillière, Patrick ; Cassegrain, Robert ; Clément ; Demozay, Didier ; Desmazières, Renaud ; Duchêne, Gérard ; Faucher, Serge ; Font-Diez, Manuel ; Fourquet, Michel ; Frize, Bernard ; Gautier, Dominique ; etc.
Impact III, Musée d'Art et d'Industrie, Saint-Etienne, été 1978
boek